All things to all people: changing perceptions of 'skill' among Britain's policy makers since the 1950s and their implications - Payne, J (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 1999)
The paper looks at how the meaning of 'skill' has broadened inconsiderably since the 1950s through an examination of the relevant policy literature. The key role of both the Manpower Services Commission (MSC) and Further Education Unit (FEU) in re-defining 'skill' in the late 1970s and 1980s is stressed. 'Core' or 'key skills', which have come to dominate contemporary education and training debates, are seen as an extension of this agenda. The new discourse of skill is also likely to have major implications for the vocational education and training (VET) system. The paper concludes by arguing that if Britain is to break out of a 'low skill equilibrium' (Finegold and Soskice 1988) and create a vibrant participatory democracy, it must shift education and training policy out of a narrow economistic focus and obsession with skills supply, and ensure universal access to a broad and integrated general and vocational education for all.